Recent advances in plant nanobionics and nanobiosensors for toxicology applications - Ansari, Mohammad Hasan Dad; Lavhale, Santosh; Kalunke, Raviraj M.; Srivastava, Prabhakar L.; Pandit, Vaibhav; Gade, Subodh; Yadav, Sanjay; Laux, Peter; Luch, Andreas; Gemmati, Donato; Zamboni, Paolo; Singh, Ajay Vikram (Current Nanoscience, 2020)
Emerging applications in the field of nanotechnology are able to solve a gamut of problems surrounding the applications of agroecosystems and food technology. Nano Engineered Material (NEM) based nanosensors are important tools for monitoring plant signaling pathways and metabolism that arc nondestructive, minimally invasive, and can provide real-time analysis of biotic and abiotic threats for better plant health. These sensors can measure chemical flux even at the single molecule level. Therefore, plant health could be monitored through nutrient management, disease assessment, plant hormones level, environmental pollution, etc. This review provides a comprehensive account of the current trends and practices for the proposed NEM related research and its (i) structural aspect, (ii) experimental design and performance as well as (iii) mechanisms of field application in agriculture and food system. This review also discusses the possibility of integration of data from NEM based nanosensors in current and emerging trends of precision agriculture, urban farming, and plant nanobionics to adopt a sustainable approach in agriculture,
Keywords: agro-ecosystems; engineered nanomaterials; nanobionics; Nanosensors; nanotechnology; nanotoxicology